Sleep Quality in an Adult American Indian Community Sample - Ehlers, Cindy L. (J Clin Sleep Med, 2017)
STUDY OBJECTIVES: Epidemiological studies have found that insufficient sleep (< 7 h/night) is more common among American Indians/Alaska Natives (AI/AN). In this study we sought to identify specific demographic, clinical, and cultural factors that may be associated with reduced sleep quality in an American Indian community sample. METHODS: Information on demography along with personal medical, psychiatric, and drinking history was obtained using the Semi-Structured Assessment for the Genetics of Alcoholism (SSAGA). Sleep quality was assessed by the Pittsburgh Sleep Quality Index (PSQI). RESULTS: The adult participants (n = 386, 54% women) had a mean ± standard deviation age of 31.35 ± 14.4 y. Higher degrees of AI ancestry, but not cultural identification, being older than 30 y, and having a high school diploma all were factors predictive of having a short sleep duration (< 6 h). The global score on the PSQI was significantly higher in those participants with a lifetime diagnosis of substance use disorders, anxiety disorders, and affective disorders. Alcohol use disorders and affective disorders were significant predictors of sleep latency whereas anxiety and affective disorders were correlated with waking more often in the night/early morning. Nicotine dependence was associated with having trouble breathing, and alcohol use disorders and anxiety disorders with bad dreams. CONCLUSIONS: Alcohol use disorders are associated with poorer quality of sleep in this population and substance use disorders were associated with different aspects of sleep than anxiety and depressive disorders. These findings add to the understanding of the interactions between sleep and substance use, anxiety, and affective disorders in an understudied and underserved population. CITATION: Ehlers CL, Wills DN, Lau P, Gilder DA. Sleep quality in an adult American Indian community sample. J Clin Sleep Med. 2017;13(3):385–391.